Application of magnetically recoverable nanocatalysts in synthesis of imidazole, thiazole, and oxazoles. Issue 18 (16th September 2020) - Zhang, Xin; Aqeel Ashraf, Muhammad; Liu, Zhenling; Zhang, Dangquan
Abstract: Imidazoles, thiazoles, and oxazoles have been identified as valuable molecules in pharmaceutical and agriculture chemistry. Molecules containing these scaffolds are excited in many natural products and biologically active molecules. During the last decade, magnetic nanomaterials have appeared as highly efficient catalysts in chemical science in general organic chemistry, because of their simple preparation, modification, and large surface area ratio. This article assists to review the application of magnetically reusable nanocatalysts in synthesis of biologically active imidazoles, thiazoles, and oxazoles. Graphical Abstract: